Cultural Approach to Religious Education in The Socio-Cultural Life of Students - Firman Mansir (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
This article describes the understanding of the educational cultural approach to religion and socio-cultural development. The results of this study indicate that there is a relationship between culture and religious education that is interrelated. With the changes and developments of an increasingly rapid era. This then leads to the fact that students as a new generation should have quality and understanding that can adapt to the progress of the times. The success of a nation can be seen and measured by the generation of students in the present and the future. Religious education cannot be separated from a cultural approach to the learning process and the formation of the social life of students. Therefore, this transformation can shape the attitudes and social souls of students. This study uses a qualitative method. Therefore, in processing data through literature review analysis of the already available datum. Meanwhile, the approach used is pedagogy, which aims to see the process of religious learning directly. Thus, it is hoped that there will be results where the new generation in this case students have good quality potential. So that they can develop their religious knowledge, and can apply it well to the fabric of the surrounding community. Be able to provide answers to various problems in the socio-cultural development of religion through an educative cultural approach.